Implementation Science for Point-of-Care Diagnostics - Mashamba-Thompson, Tivani P. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the application of implementation science methods to enable the rapid uptake and sustainable implementation of new diagnostics into routine health practices to strengthen health systems.Diagnostics are essential for the success of universal health coverage and improved health outcomes. The increased development and deployment of diagnostics for use at the point of care will not guarantee improved access to diagnostics and health outcomes if their implementation is not optimized. Optimal implementation will need to be guided by theories and methods that aim to promote evidence-based practices and findings of research into routine practice, taking into consideration quality systems and contexts.